ANALISIS GENERATIF-TRANSFORMATIF DALAM HADITS NABI TENTANG KEUTAMAAN ILMU - Ashief El Qorny (Pusat Studi Kependidikan (PSKp) Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Sains Al-Qur'an, 2018)
The Hadith is source of both in establishing Islamic law. Hadith is a product of language is the companions of the Prophet to convey. However, there is a hadith which has same meaning, but has a different in chief. The purpose of this article is to analyze the hadith based on generative transformative theory by AN. Chomsky. In this analysis of two sampled hadiths about the primacy of science that has distinction of the editor, so it can be determined by each narrators of hadith.